Emigration of Polish healthcare system workers, especially to Great Britain - Wyrozębska, Agnieszka; Matysiak, Agata; Tatara, Tomasz (Polish Journal of Public Health, 2009)
Introduction. European healthcare systems struggle with dynamic changes and demographic trends that impose growing demand for healthcare services in highly developed countries. Due to limited resources and funding, sound balance between demand and supply has to be found. Aim. The aim of the paper is to analyse migration of Polish health professionals with special attention paid to extensive migration to the United Kingdom. Results. The first part of the paper shows main factors inducing young Polish workers to look for a job in foreign countries as well as presents trends and diversion in migration due to access of Poland to the European Union. The key incentive to Polish healthcare professionals to start up working abroad are higher wages, therefore the second part of the paper presents a comparison of public health professionals’ salaries in Poland and UK. Conclusion. Taking into account great importance of healthcare professionals to provide societies with desired, high standard of living, grave problem arises due to expected shortages of healthcare professionals. Therefore, broad, negative consequences of brain drain in Polish healthcare system will be also analyzed.